2014
DOI: 10.1186/1471-2393-14-180
|View full text |Cite
|
Sign up to set email alerts
|

Child feeding knowledge and practices among women participating in growth monitoring and promotion in Accra, Ghana

Abstract: BackgroundChild undernutrition and poor feeding practices remain a concern in Ghana. The Growth Monitoring and Promotion (GMP) programme seeks to empower mothers to provide appropriate child care. Although the program has been implemented in Ghana for over four decades, little is known about its impact on child feeding outcomes. The current study assessed the association between GMP exposure and mothers' child feeding knowledge and practices in the Accra Metropolitan Area (AMA), Ghana.MethodsA cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
62
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 27 publications
22
62
10
1
Order By: Relevance
“…In contrast to the EBF rate of 51.7% in the present study, Gyampoh, et al [16] in their study among Ghanaian women reported a much higher EBF rate of 80.1%. The reason for this difference may be because the present study assessed the overall practice of EBF among the children less than six months whereas Gyampoh, et al [16] assessed the practice of EBF in only the preceding 24 hours. Thus several children who were on mixed feeding would have been regarded as being exclusively breastfed if they were exclusively breastfed in the preceding 24 hours to their study.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In contrast to the EBF rate of 51.7% in the present study, Gyampoh, et al [16] in their study among Ghanaian women reported a much higher EBF rate of 80.1%. The reason for this difference may be because the present study assessed the overall practice of EBF among the children less than six months whereas Gyampoh, et al [16] assessed the practice of EBF in only the preceding 24 hours. Thus several children who were on mixed feeding would have been regarded as being exclusively breastfed if they were exclusively breastfed in the preceding 24 hours to their study.…”
Section: Discussioncontrasting
confidence: 94%
“…Reports have shown that despite continuous breastfeeding messages and the launch of the Global Strategy for Infant and Young Child Feeding over ten years ago, the EBF rate in Nigeria is still very low [13,15]. Complementary feeding practices are also poor [16,17]. Unfortunately poor complementary feeding practices undermine the benefits of exclusive breast feeding and annually, an estimated 600,000 lives are lost globally from not continuing breastfeeding with proper complementary feeding [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with study findings in Mumbai [39] and Pakistan [37]. Yet, this finding is lower than the study findings in other parts of Ethiopia [33, 40], Ghana [41] and India [31, 42]. This could be due to difference in study settings as this study was conducted in slum areas hence the participants were poor and with low educational status.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to that of the study conducted in Accra, Ghana [22]. This indicates and strengthens those different sociodemographic factors like mothers' age, husbands' education, and source of information and economic factors like household income could affect dietary diversity significantly.…”
Section: Discussionsupporting
confidence: 89%